2015
DOI: 10.1007/s10482-015-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, invasion, intracellular survival and cytotoxic activity of strains of Aeromonas spp. in HEp-2, Caco-2 and T-84 cell lines

Abstract: The genus Aeromonas contains important pathogen for both humans and other animals, being responsible for the etiology of intestinal and extraintestinal diseases. The pathology caused by these bacteria involves several virulence factors, such as the ability to produce toxins, adhesion and invasion. The properties conferred by these factors have been extensively studied in experiments of interaction between bacterial strains and cell culture. We evaluate the interaction of eight Aeromonas spp. strains, previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Many studies of pathogenesis and virulence in Aeromonas have been carried out in recent years using in vitro cell lines ( Table 3). The ability of Aeromonas to adhere, invade, and produce cytotoxicity has been defined, mainly following A. hydrophila and A. caviae infections, using human larynx carcinoma (HEp-2) and human Caucasian colon adenocarcinoma (Caco-2) cells [289,[308][309][310]. Ghatak et al [309] analyzed the cytotoxicity of 55 strains of Aeromonas using four cell lines, African green monkey kidney (Vero), Madin Darby bovine kidney (MDBK), baby hamster kidney (BHK-21), and lymphoblast B mono lymphoblast (B95a) cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of pathogenesis and virulence in Aeromonas have been carried out in recent years using in vitro cell lines ( Table 3). The ability of Aeromonas to adhere, invade, and produce cytotoxicity has been defined, mainly following A. hydrophila and A. caviae infections, using human larynx carcinoma (HEp-2) and human Caucasian colon adenocarcinoma (Caco-2) cells [289,[308][309][310]. Ghatak et al [309] analyzed the cytotoxicity of 55 strains of Aeromonas using four cell lines, African green monkey kidney (Vero), Madin Darby bovine kidney (MDBK), baby hamster kidney (BHK-21), and lymphoblast B mono lymphoblast (B95a) cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Moreover, Merino et al [289] demonstrated by the generation of mutants that the flagella glycosylation in A. hydrophila plays an extremely important role in the adhesion to Hep-2 cells and in biofilm formation. In a recent study, Dos Santos et al [308] evaluated the capacity of Aeromonas species to adhere, invade, survive, and produce cytotoxicity through the use of three different cell lines: HEp-2, Caco-2, and human colorectal adenocarcinoma (T-84). The results suggested that cytotoxicity and adhesion would depend on the type of cell line analyzed, indicating that the majority of Aeromonas strains survived in the T-84 cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The virulence of Aeromonas spp. has been considered multifactorial and associated with different toxins-aerolysin, hemolysin, lipases, and enterotoxins-some of them delivered by different types of secretion systems as well as produced through a signal molecules such as N-acyl homoserine-lactone (AHLs) by a phenomenon defined as quorum sensing, which results in the colonization, invasion, and proliferation of the bacteria during the infectious process (9)(10)(11)(12). However, the development of the infection depends on the immunity of the host, which is divided into two types: innate and adaptive (13).…”
Section: Introductionmentioning
confidence: 99%
“…This process is characterized by the activation of different types of caspase enzymes and contributes to the activation of pro-inflammatory cytokines, recruits more immune cells, and finally activates an inflammatory cascade in the tissue (14). In the last years, few studies have investigated the expression of several innate immune-related genes against A. hydrophila, A. veronii, and Aeromonas salmonicida in different cell lines or animal models (mice and fish) (12,(21)(22)(23)(24). The majority of the studies has been performed with cell lines obtained from animals, with the exception of two cell lines (T-84 and WLR-68) obtained from the human colon (12,24).…”
Section: Introductionmentioning
confidence: 99%
“…The Vibrio strains were previously characterized by cytotoxic activities. It has been described that the extracellular products of Vibrio harveyi CAIM 1792 strain, isolated from infected shrimp, L. vannamei, exhibited a strong cytotoxic activity to HELA cell line after 6 and 24 h inoculation [51]. In addition, it was reported that 10 −4 dilutions of the culture filtrate of Vibrio cholerae, Vibrio parahemolyticus, and Vibrio vulnificus showed greater toxic potential to Vero cells [52].…”
Section: Discussionmentioning
confidence: 99%